The role of magnetic resonance enterography and diffusion-weighted imaging in pediatric inflammatory bowel disease compared to endoscopic and clinical activity scores: pilot study - Gehad Ahmad Saleh; Ahmed Abdel Khalek Abdel Razek; Sara Ibrahim Awad; Mohamad Abd El Rahaman Shokeir; Ahmed Megahed (The Egyptian Journal of Radiology and Nuclear Medicine, 2023)
Abstract Background Inflammatory bowel disease (IBD) is considered as significant cause of morbidity in children with a global rise in its pediatric onset recently. Our study aimed to assess the facility of magnetic resonance enterography (MRE) and diffusion-weighted imaging (DWI) to identify the activity of pediatric IBD in correlation with clinical and endoscopic activity scores. Twenty-four patients of IBD who underwent clinical examination, ileocolonoscopy and MRE and DWI within less than 14 days were prospectively included. For all Crohn’s cases (9/24), the simplified endoscopic activity score for Crohn’s disease (SES-CD) and magnetic resonance enterography global score (MEGS) were acquired, while for all UC (15/24) cases, MRE score and Mayo endoscopic score were calculated. Sensitivity and specificity of MRE for detection disease activity against clinical and endoscopic scores were compared. Pathological reference for disease activity was based on assessment for mucosal inflammatory changes on endoscopic biopsy in all cases. Results There was a perfect inter-observer agreement (kappa 0.81–1) regarding wall thickening and mural edema, with substantial agreement (kappa 0.61–0.8) for MRE severity score, mural diffusion restriction, mesenteric edema and vascular congestion, while mural enhancement and for number of active LNs revealed moderate agreement (kappa 0.41–0.6). There was a significant positive correlation between MEGS and SES-CD in Crohn’s cases as well as between Mayo endoscopic score and MRE severity in UC cases (r = 0.970, p > 0.001 and r = 0.544, p = 0.036, respectively). MRE compared to endoscopic findings and clinical activity scores revealed high accuracy (95.8%) with 87.5%, 80%, 96% and 94.1% for sensitivity, specificity, PPV and NPV, respectively. Conclusion MR enterography is a noninvasive reliable imaging modality of high accuracy for the diagnosis of pediatric IBD severity compared to endoscopic activity scores and pathological severity.